2011
DOI: 10.1128/mbio.00204-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of an Outbreak of Carbapenem-Resistant Enterobacteriaceae Reveals Intergenus KPC Carbapenemase Transmission through a Promiscuous Plasmid

Abstract: Carbapenem-resistant Enterobacteriaceae (CRE) have emerged as major causes of health care-associated infections worldwide. This diverse collection of organisms with various resistance mechanisms is associated with increased lengths of hospitalization, costs of care, morbidity, and mortality. The global spread of CRE has largely been attributed to dissemination of a dominant strain of Klebsiella pneumoniae producing a serine β-lactamase, termed K. pneumoniae carbapenemase (KPC). Here we report an outbreak of KP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
159
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 29 publications
8
159
3
2
Order By: Relevance
“…Given that bla KPC is found on plasmids that are transmissible among Enterobacteriaceae and can produce novel CRKP strains (24,25) The heterogeneity in wzi types and bla KPC variants among ST258 isolates encountered in our study is consistent with emerging literature on variability in capsule types and associated resistance determinants in this ST (10,11,26). We found that bla was almost entirely restricted to wzi154-positive ST258 CRKP isolates, whereas bla KPC-2 was detected in isolates with several sequence and wzi alleles.…”
Section: Discussionsupporting
confidence: 79%
“…Given that bla KPC is found on plasmids that are transmissible among Enterobacteriaceae and can produce novel CRKP strains (24,25) The heterogeneity in wzi types and bla KPC variants among ST258 isolates encountered in our study is consistent with emerging literature on variability in capsule types and associated resistance determinants in this ST (10,11,26). We found that bla was almost entirely restricted to wzi154-positive ST258 CRKP isolates, whereas bla KPC-2 was detected in isolates with several sequence and wzi alleles.…”
Section: Discussionsupporting
confidence: 79%
“…Few clinical laboratories have the capability of identifying the mechanism of carbapenem resistance, and yet this information can be exceedingly useful to outbreak investigations by identifying patients colonized with CRE that harbor the same resistance mechanism and are thus potentially part of an outbreak. Furthermore, carbapenemase genes are harbored on highly mobile genetic elements, and the ability to detect the spread of a particular gene may aid in identifying plasmid-mediated outbreaks that occur across patients and genera of the Enterobacteriaceae (21).…”
mentioning
confidence: 99%
“…In particular, Klebsiella pneumoniae sequence type 258 (ST258) and its derivatives carrying plasmid-borne bla KPC carbapenemase genes have spread to cause outbreaks globally (3)(4)(5)(6)(7)(8)(9)(10). Some evidence suggests that CRE outbreaks could alternatively involve the primary transmission of carbapenemase-encoding plasmids or other mobile elements among genetically heterogeneous populations of bacteria, although this has not been demonstrated to be a dominant epidemiologic mechanism to date (11)(12)(13)(14)(15)(16)(17)(18). In areas of high endemicity, it is also possible for multiple unrelated plasmids mediating carbapenem resistance to be present concurrently among bacterial strains circulating during a given outbreak, leading to potentially complex transmission chains.…”
mentioning
confidence: 99%